Structure Characterization of Escherichia coli Pseudouridine Kinase PsuK - Li, Xiaojia; Li, Kangjie; Guo, Wenting; Wen, Yan; Meng, Chunyan; Wu, Baixing (Frontiers in Microbiology, 2022)
Pseudouridine (Ψ) is one of the most abundant RNA modifications in cellular RNAs that post-transcriptionally impact many aspects of RNA. However, the metabolic fate of modified RNA nucleotides has long been a question. A pseudouridine kinase (PsuK) and a pseudouridine monophosphate glycosylase (PsuG) in E. coli were first characterized to be involved in pseudouridine degradation by catalyzing the phosphorylation of pseudouridine to pseudouridine 5’-phosphate (ΨMP), and further hydrolyzing 5′-ΨMP to produce uracil and ribose 5’-phosphate. Recently, their homolog proteins in eukaryotes were also identified, which were named PUKI and PUMY in Arabidopsis. Here, we solved the crystal structures of apo-EcPsuK and its binary complex with Ψ or N1-methyl-pseudouridine (m1Ψ). The structure of PsuK showed a homodimer conformation assembled by its β-thumb region. PsuK has an appropriate binding site with a series of hydrophilic and hydrophobic interactions for Ψ. Moreover, our complex structure of PsuK-m1Ψ suggested the binding pocket has an appropriate capacity for m1Ψ. We also identified the monovalent ion binding site and potential ATP binding site. Our studies improved the understanding of the mechanism of Ψ turnover.